2012
DOI: 10.21236/ada557547
|View full text |Cite
|
Sign up to set email alerts
|

A New Error Bound for Reduced Basis Approximation of Parabolic Partial Differential Equations

Abstract: We consider a space-time variational formulation for linear parabolic partial differential equations. We introduce an associated Petrov-Galerkin truth finite element discretization with favorable discrete inf-sup constant β δ : β δ is unity for the heat equation; β δ grows only linearly in time for non-coercive (but asymptotically stable) convection operators. The latter in turn permits effective long-time a posteriori error bounds for reduced basis approximations, in sharp contrast to classical (pessimistic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 6 publications
3
51
0
Order By: Relevance
“…In addition, these methods can remove spurious temporal modes (e.g., unstable growth, artificial dissipation) from the state space, which can in principle lead to more accurate long-time responses. Further, space-time reduced-basis ROMs [45,46,50,49] are equipped with error bounds that are observed to grow linearly (rather than exponentially) in the final time. While these approaches are quite promising, they exhibit several drawbacks in terms of applicability to general large-scale nonlinear dynamical systems.…”
mentioning
confidence: 99%
“…In addition, these methods can remove spurious temporal modes (e.g., unstable growth, artificial dissipation) from the state space, which can in principle lead to more accurate long-time responses. Further, space-time reduced-basis ROMs [45,46,50,49] are equipped with error bounds that are observed to grow linearly (rather than exponentially) in the final time. While these approaches are quite promising, they exhibit several drawbacks in terms of applicability to general large-scale nonlinear dynamical systems.…”
mentioning
confidence: 99%
“…for all 1 ≤ p ≤ P , where D k is defined in (34) and E (p) k in (36). As a consequence, there is only one term composing the matrices B and B fdPG that differs, namely the time matrix in the double summation over p, p ′ where this matrix is M…”
Section: Methods 2: Fully Discrete Petrov-galerkin Methodsmentioning
confidence: 99%
“…Remark 2.4 (Heat equation). Sharp estimates of the inf-sup constant β for the heat equation (with µ(t) ≡ 1 on I so that α = M = 1 and κ = 0) can be found in [36,10] using the above norms.…”
Section: Moreover Using Again the Coercivity Of A(t) And The Boundedmentioning
confidence: 99%
“…Nevertheless, uniform stability was not proven and in [2] it was even shown that indeed the Crank-Nicolson method is generally not a stable space-time method. The interpretation of essentially time-stepping methods via the spacetime formulation was also exploited for reduced basis approximations [38,39] as well as for (quantized) tensor train (QTT) low rank tensor approximations [23] just to mention a few. In that regard, we would like to mention [38,39] in the context of the Crank-Nicolson method and [31] in the context of the discontinuous Galerkin method for the heat equation.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of essentially time-stepping methods via the spacetime formulation was also exploited for reduced basis approximations [38,39] as well as for (quantized) tensor train (QTT) low rank tensor approximations [23] just to mention a few. In that regard, we would like to mention [38,39] in the context of the Crank-Nicolson method and [31] in the context of the discontinuous Galerkin method for the heat equation. These works give stability results by introducing subspace-dependent norms but not directly with respect to the natural space-time norms.…”
Section: Introductionmentioning
confidence: 99%